A study on the effects of the alcoholic extract of the aerial parts of Echinophora platyloba on the activity of pituitary-gonadal axis in hypercholesterolemic rats - Sokhandani Mansour, Zarei Ali, Changizi-Ashtiyani Saeed (Journal of Applied Pharmaceutical Science, 2016)
The present experimental study was carried out to examine the effects of the alcoholic extract of the aerial parts of Echinophora platyloba on prolactin (PRL) levels and the activity of pituitary-gonadal axis in animal model. Forthy male wistar rats were divided into five groups: control group with normal diet, hypercholesterolemic group with fat diet, and three experimental groups which received Echinophora platyloba alcoholic extract as gavage at the minimum dose of 100, the average dose of 200, and the maximum dose of 400 mg/kgbw over a period of 21 days. At the end of the period, to assess the levels of PRL, cholesterol, testosterone, luteinizing hormone (LH) and follicle stimulating hormone (FSH), blood samples were taken and data were analyzed. The levels of testosterone and cholesterol in hypercholesterolemic group compared to the control, showed a significant decrease and increase, respectively (P≤0.05). Echinophora platyloba extract caused significant increases in testosterone, PRL and a significant decrease in cholesterol levels (P≤0.05), however, it had no significant effect on the levels of LH and FSH. The results of this study showed that the consumption of alcoholic extract of Echinophora platyloba is effective in reducing serum cholesterol, increasing testosterone production and enhancing sexual performance.
Keywords: Echinophora platyloba, Prolactin, Pituitary gland, Testosterone, Rats.